Effect of an Impervious Core Constructed into a Large Earth Dam on the Quantity of Seepage (University of Thi-Qar Journal for Engineering Sciences, 2011)
Impervious core is used in zoned earth dam to reduce the quantity of seepage through the body of the dam and to relief part of risk of piping and erosion in the downstream side. This paper presents cases study of the effect of core permeability, thickness and location on the flow through large earth dam. Finite element method was used to solve the problem of flow of incompressible fluid which is governed by Laplace equation. A considerable range of shell permeability to core permeability was used. The study has shown that quantity of seepage was reduced as ratio of shell to core permeability increases. The reduction in seepage continues to a limited value of core permeability after which the effect decreases. Doubling the core base thickness reduces the quantity of seepage highly and inclination of core towards upstream side slightly increases the quantity of seepage.